The institution of the Hasmonean high priesthood - Babota, Vasile (Journal for the study of Judaism, 2014)
3. The Edicts of Antiochus III for Jews and the Jerusalem Temple3.1. The Royal strategos and archiereus Ptolemy and the Jerusalem High Priest; 3.2. King Antiochus III and the Judean Authorities; 3.3. Antiochus III, the Jewish ethnos, and the Jerusalem Temple; 4. King Seleucus IV and the Royal archiereus Olympiodorus; 5. The Jewish High Priest Onias III and the Inner Struggles; 6. The Jewish High Priest Jason and the Hellenizing Reform; 6.1. The Institution of the Gymnasium and of the "Antiocheans"; 6.2. The Jewish High Priesthood for Sale: A Hellenistic Innovation